2017
DOI: 10.5935/0004-2749.20170070
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anterior segment and optic nerve head parameters in healthy subjects

Abstract: In nonglaucomatous eyes, the dimensions and shape of the ONH may be related to anterior segment morphology. Therefore, it may be helpful to take anterior segment parameters into consideration in evaluating the OHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…They reported significantly larger disc and cup areas, thinner RNFL measurement, and deeper cup depth in KCN patients than non-KCN individuals. Their findings were consistent with previous studies that reported the same results on thin corneas [10,66,69]. They speculated that these associations might be attributed to the continuous collagen tissue extension of the cornea and sclera.…”
Section: Keratoconus and Optic Nerve Head Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…They reported significantly larger disc and cup areas, thinner RNFL measurement, and deeper cup depth in KCN patients than non-KCN individuals. Their findings were consistent with previous studies that reported the same results on thin corneas [10,66,69]. They speculated that these associations might be attributed to the continuous collagen tissue extension of the cornea and sclera.…”
Section: Keratoconus and Optic Nerve Head Parameterssupporting
confidence: 92%
“…This lack of research often leads to the misconception that KCN is simply an anterior segment disease; however, KCN can be accompanied by posterior segment abnormalities. Possible interactions between the structural properties of the posterior and anterior segments of the eye have been hypothesized as there are continuous extensions of specific ocular structures that span from the anterior to the posterior segments [10]. Accordingly, it has been reported that posterior pole retinal thicknesses may change with KCN severity [11].…”
Section: Introductionmentioning
confidence: 99%
“…7,27 It has been theorised that the ocular structures in the two segments of the eye are structurally related owing to the continuity of some of the ocular structures from the anterior segment into the posterior segment. 29 As keratoconus has been reported with other ocular conditions, including retinitis pigmentosa, 30 Leber's congenital amaurosis, 31 choroidal neovascularisation, 32 central serous chorioretinopathy 33 and Goldmann-Favre disease, 34 investigating the posterior ocular segment in individuals with keratoconus is important particularly when corneal transplantation (penetrating keratoplasty and/or deep anterior lamellar keratoplasty) is considered as a form of management. 32,35 Therefore, the aim of this study was to investigate macular thicknesses in patients with keratoconus.…”
Section: Introductionmentioning
confidence: 99%